Evaluasi Dampak Pelatihan Dan Keberagaman - Devina Putri Meilia; Muhammad Ravi Khairul Umam; Siti Nur Aini; Putriana; Fitratul Amaliyah (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study investigates the relationship between training assessment and diversity management in an organization and emphasizes how important it is to combine both to improve employee performance, innovation, and creativity. The results show that diversity can be a strategic tool that increases productivity if managed well. However, without effective management, diversity can lead to conflict and dissatisfaction. The study found shortcomings in evaluation practices that are often limited to the final phase by analyzing needs in the planning stage, monitoring during implementation, and post-training evaluation. According to the study, organizations can develop inclusive and sustainable diversity policies by conducting comprehensive evaluations at every stage of the process. By combining training evaluation with diversity management, organizations can create a more cooperative work environment, which in turn will improve employee health and performance. Data were obtained through a literature review from various academic sources and analyzed using a qualitative descriptive approach. The results show that the success of diversity management depends on good corporate governance and diversity training that is appropriate to the local context. The development of broader training programs and regular diversity assessments are suggestions for future research.